2015
DOI: 10.1111/age.12385
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of miRNAs in the ovaries of a highly prolific sheep breed

Abstract: Until recently, there have been few studies concerning miRNAs or miRNA-mediated biological processes in sheep (Ovis aries). In the present study, we used a deep-sequencing approach to examine ovarian miRNAs and the mRNA transcriptomes in two ewes of a highly prolific breed, Finnsheep. We identified 113 known sheep miRNAs, 131 miRNAs conserved in other mammals and 60 novel miRNAs, the expression levels of which accounted for 78.22%, 21.73% and 0.05% of the total respectively. Furthermore, the 10 most abundantly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 22 publications
1
13
0
Order By: Relevance
“…After 2–3 weeks of pregnancy, the ewes were slaughtered to collect the tissue biopsies of corpus luteum (CL) and endometrium for inclusion in this study. Procedures for RNA extraction, sample quality control measurements and sequence library preparation have been described previously (Hu et al, 2015; Pokharel et al, 2020). High‐quality libraries of miRNA were sequenced with an Illumina HiSeq 2000 system using single‐end (1 × 50) sequencing strategy.…”
Section: Figurementioning
confidence: 99%
“…After 2–3 weeks of pregnancy, the ewes were slaughtered to collect the tissue biopsies of corpus luteum (CL) and endometrium for inclusion in this study. Procedures for RNA extraction, sample quality control measurements and sequence library preparation have been described previously (Hu et al, 2015; Pokharel et al, 2020). High‐quality libraries of miRNA were sequenced with an Illumina HiSeq 2000 system using single‐end (1 × 50) sequencing strategy.…”
Section: Figurementioning
confidence: 99%
“…In a genome-wide transcriptome analysis of different breeds with high-and lowfecundity sheep, multiple candidate genes, such as BAX, BAD, NDUFA13, CAV1, LOC101117112, PAX8 and IFI6; and miRNAs, such as oar-miR-665-5p, oar-miR-411a-5p, oar-miR-1197-3p and oar-miR-134-3p, were shown to be critical for sheep fecundity, and signaling pathways Wnt, MAPK and G-protein were shown to be potentially critical for regulating sheep fecundity and prolificacy [53][54][55] . Furthermore, an RNA-seq study with multiple sheep breeds revealed that PRLR, PGR, ESR2, CYP19A1, CYP11A1, HSD17B12, INHBA, and BMP receptors (BMPR1B and BMPR2) genes could be involved in follicular development or control of ovulation, and TGF-b and PPAR pathways might regulate female reproduction [56,57] .…”
Section: Reproductive Traitsmentioning
confidence: 99%
“…For example, bone morphogenetic protein receptor 1B (BMPR1B) encodes a member of the bone morphogenetic protein (BMP) receptor family of transmembrane serine/threonine kinases that belongs to the transforming growth factor b (TGFb) receptor family. Through QTL fine mapping and deep-sequencing approaches, BMPR1B has been demonstrated to be a strong candidate gene for the prolificacy traits in sheep [57,87,88] . Also, BMPR1B knockout mice showed irregular estrous cycles and an impaired pseudo-pregnancy response; meanwhile, the level of mRNA for cyclooxygenase 2, an enzyme required for cumulus expansion, was increased [89] .…”
Section: Box 1: Workflow Of Identification Validation and Applicatiomentioning
confidence: 99%
“…Until now, several attempts have been made to map quantitative trait loci or detect causal mutations responsible for phenotypic variation of reproduction in sheep employing techniques such as genome‐wide association studies (Gholizadeh, Rahimi‐Mianji, Nejati‐Javaremi, Koning, & Jonas, ; Lv et al, ; Wang et al, ), RNA‐Seq analyses (Chen et al, ; Hu et al, ) and methylated DNA immunoprecipitation sequencing (Cao et al, ). In the study herein, we applied nucleotide diversity (Pi) and F ST statistical methods to compare the whole genome sequences of the Romanov sheep with those of the Assaf, Awassi, Cambridge and British du cher breeds to explore the genetic mechanisms underlying variation in litter size and to find novel candidate genes in the genomic regions under selection.…”
Section: Introductionmentioning
confidence: 99%